A social media study: the state civil apparatus commission’s online presence - Suswanta; Irfandi Pratama; Al Fauzi Rahmat (Jurnal Studi Komunikasi, 2024)
The State Civil Apparatus (ASN) Law exists as a bureaucratic reform movement to strengthen institutions. One of which is the formation of the State Civil Apparatus Commission (KASN) to monitor and evaluate ASN management. This enthusiasm is present in filling high bureaucratic positions not based on a merit system that is in addition to the issue of bureaucratic politicisation, which refers to violations of the code of ethics. Still, regarding this issue, the urgency of KASN is often questioned to the point of discussing its dissolution. Thus, this research examines the existence of KASN using qualitative methods with a descriptive approach, using primary data obtained from KASN's Twitter social media account with the username @KASN_RI by capturing it using Ncaputre software with data results from 2017-2021. For data analysis, the researchers used Software Nvivo 12 Plus with the Word Cloud tools menu, limited to 100 display words with three minimum lengths. Research findings show that KASN is more active in providing information on Twitter social media regarding merit system policies, neutrality, and ASN codes of ethics and behaviour. This is in line with the findings, which show that the words that frequently appear are KASN and ASN. Then, to increase the visibility of information, mention working partners, including the PANRB and BKN ministries. Then, the hashtags used are varied, but their use does not explicitly indicate a related event, so the hashtag function is not utilised correctly.